Implementation of the AHP-SMARTER Method in the Decision Support System for Giving Sanctions for Violation of Student Disciplines - Fadli, Sofiansyah; Ashari, Maulana; Asyari, Hasyim; Pardiansyah, Ahmad Susan (Universitas Trilogi, 2022)
Violations of school rules are often carried out by students, including lack of respect for teachers, students who are not on time, often late for class, skipping classes, jumping fences, smoking and not paying attention to the rules and other regulations in school. This study aims to build a decision support system for sanctions for violations of student discipline that has the ability to analyze each of the criteria and sub-criteria that have been determined by the school. In this case, students who violate school rules will be punished and given sanctions so as to provide an output value of priority intensity which results in a system that provides an assessment of violations against students. The method used in building this decision support system is by combining the Analytical Hierarchy Process (AHP) method and the Simple Multi Attribute Rating Technique Exploiting Rank (SMARTER) method. Weighting criteria using the AHP method and for ranking using the SMARTER method. The system created can be used to assist in processing data on violations of school rules. With this decision support system, it is hoped that policy makers will have no difficulty in determining what types of actions and sanctions will be given to students who violate school rules.